PENGEMBANGAN BUKU AJAR EKONOMI INDONESIA DENGAN MENGINTERNALISASIKAN NILAI-NILAI KEINDONESIAAN PROGRAM STUDI PENDIDIKAN EKONOMI IKIP BUDI UTOMO - Novi Eko Prasetya; Miftah Rakhmadian (Jurnal Pendidikan Ilmu Sosial, 2019)
The focus of developing this Indonesian economic textbook is to internalize the character of Indonesian values, Indicators of Indonesian values include; nationalism, love for the motherland and democracy. Achievement of learning is demonstrated by the ability to conduct in-depth study of economic problems in Indonesia, as well as the activity and critical thinking skills of students in the learning process. Indonesian economic textbooks are presented with the scope of contextual problems so that students can analyze issues related to Indonesia's economic conditions. The aim of the Indonesian economic textbook is to reconstruct the concept between theory and practice by internalizing Indonesian values. The discussion in each subject becomes the main point of planting the character of Indonesian values. The research method used is R D (Research and Development). The teaching book material consists of 6 subjects, each of which has internalized the Indonesian values.